“Where Is My Tribe”? Queer Activism in the Occupy Movements - Pérez Navarro, Pablo (2016)
From the Arab Spring to the Umbrella Revolution, the last cycle of citizen protests has widely shared the strategy of occupying public spaces through the settlement of protest camps. Although one might imagine a homogeneous unity amongst the protesters, these encampments have been the scenario of multiple inner conflicts in relation with different vectors of oppression. This article discusses the conflicts faced and the coalition-building developed by queer activists in different encampments, with a focus on the relation between the occupation of queer spaces and the space of the protest as a whole. The Foucauldian concept of heterotopia is used here as a guide in order to understand the ambivalences and inner tensions of the space of the protest without losing, nor idealizing, the utopian impulse of these movements.